Dampak Potensial Penggunaan ChatGPT (Generative Pre-training Transformer)/AI (Artificial Intelligence) untuk Peningkatan Efisiensi Pelayanan dan Edukasi Pasien Diabetes Melitus - Eric Septian Prawira; Hikmah, Nurul (PT Kalbe Farma Tbk., 2024)
ChatGPT (generative pre-training transformer) is an artificial intelligence technology from OpenAI, which functions as a chatbot with human-like conversational capabilities. This emphasizes the potential of ChatGPT in improving health services, such as diabetes mellitus health services. The challenges are factors such as a lack of human resources and low public awareness. ChatGPT integration is proposed to improve the effectiveness of healthcare services, offering diagnostic support, and educational resources for diabetes awareness.